SUKU ANAK DALAM BATIN 9 DAN KONFLIK SERIBU HEKTAR LAHAN SAWIT ASIATIC PERSADA - Dwi Wulan Pujiriyani; Widhiana Hestining Puri (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
This paper seeks to explore the case of conflict within palm oil plantation-local people partnership involving SADBatin 9 group with palm oil company. Bungku village was the site chosen to take this issue comprehensively.The expansionofpalm oil plantationshave led totheloss ofliving territoryto developtheir social system. Conflictsarisenot onlyverticalbutalsohorizontal. Amongst the Inner SAD 9 itself, each fighting for its sovereignty emerged. SAD groups which were impoverishedby imbalanced control structure eventually have to deal with a part of their own group which slowly became part of the newruling capital group. The palm oil skipper that came from a group of local residents as well as newcomers were the form of theemerging plantation power. In the context of adverse incorporation, they were part of the group that get benefit from thepresence of palm oil plantation. Involvement or integration of this group in the oil business scheme has allowed them toaccumulate new capital sources. This group could accumulate greater profits from palm-oil they collect from small farmers.Key words: Suku Anak Dalam, palm oil, conflict, partnership